Analysis of the Impact of Technological Changes on Traditional Business Model - Humaira, Johan Ariel (Inspirasi & Strategi (INSPIRAT): Jurnal Kebijakan Publik & Bisnis, 2024)
This research investigates the impact of technological changes on traditional business models across various industries, focusing on how organizations adapt to digital disruption and leverage innovation for competitive advantage. Through a mixed-methods approach, including qualitative interviews, quantitative surveys, and case studies, the study identifies key themes such as enhanced agility, customer-centric strategies, and the importance of workforce development. Findings reveal that organizations embracing technology experience improved responsiveness and revenue diversification; however, challenges such as cultural resistance and long-term sustainability concerns persist. The research highlights the critical role of human factors in successful digital transformation, emphasizing that effective change management and employee engagement are essential. By comparing findings across sectors, the study underscores the necessity for tailored strategies that address industry-specific dynamics. Ultimately, this research contributes to a nuanced understanding of digital transformation, offering actionable insights for businesses aiming to navigate the complexities of the digital economy while ensuring long-term viability.